Uji Aktivitas Inhibitor Xanthin Oksidase dari Fraksi Ekstrak Etanol Herba Peperomia pellucida - Prihastuti, Angelina Ajeng; Wijaya, Sumi; Hartanti, Lanny (Faculty of Pharmacy, Widya Mandala Surabaya Catholic University, Indonesia, 2017)
Peperomia pellucida (L.) Kunth known as Suruhan is a potential medicinal plants, used traditionally to treat gout. Suruhan herb (Peperomia pellucida (L.) Kunth) had been studied in vivo, and found to be able to lowering uric acid levels in the blood. Ethanol extract of Peperomia pellucida (L.) Kunth herb also had been studied in vitro, and found to be potential to inhibit xanthine oxidase. The purpose of this study is to know the potential of fraction from ethanol extract of Peperomia pellucida (L.) Kunth. herb as xanthine oxidase inhibitor compared to allopurinol and its ethanolic extract. Ethanol extract of Peperomia pellucida (L.) Kunth herb was obtained by percolation method using ethanol 96%. The fractionation is done by column chromatography method using silica as stationary phase and n-hexane, n-hexane-ethyl acetate, ethyl acetate, ethyl acetate-ethanol, and ethanol as mobile phases. The fraction which contained flavonoid compounds was tested its xanthine oxidase inhibition potency using UV spectrophotometer at λ 290 nm. The absorbance was observed every 10 seconds for 10 minutes for extract and fraction with the concentration of 0.25 ppm - 5 ppm, while allopurinol was determined with the concentration of 0.2 ppm - 3.2 ppm. The result showed that ethyl acetate-ethanol fraction potentially inhibited xanthine oxidase with IC50 value of 5.00 ± 0.06 ppm, while ethanolic extract of Peperomia pellucida (L.) Kunth herb and allopurinol have IC50 value 0.33± 0.07 ppm and 0.84 ± 0.02 ppm respectively. Thus it can be concluded that ethyl acetateethanol fraction had potential as xanthine oxidase inhibitor, but the potential is lower than the ethanolic extract of Peperomia pellucida (L.) Kunth herb.